PERKAWINAN DALAM PERSPEKTIF HUKUM DAN AGAMA (KAJIAN ATAS JIWA RELIGIUS UUP DAN PRAKTIK PERKAWINAN CAMPURAN INTERRELIGIUS) - Yunanto, Yunanto (Fakultas Hukum, Universitas Diponegoro, 2017)
The legitimacy of marriage always refers to two laws, religious law and state law. The emphasis on religious law brings consequences to the ban on marriage that is done outside of religious law. Recording of marriage as a manifestation of state law carries the implication that the marriage recording agency only serves to record a marriage when marriage has been committed under religious law. The concept of legitimacy of marriage thus becomes inconsistent when interreligious mixed marriage practices occur. Keywords: Marriage, interreligius